2018
DOI: 10.1097/md.0000000000010007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic gastrectomy for elderly patients with gastric cancer

Abstract: Background:Laparoscopic gastrectomy (LG) has been widely applied in patients with gastric cancer (GC). However, the safety and application value of LG in elderly patients with GC was still unclear. In this study, we aimed to evaluate the feasibility and safety of LG for elderly patients with GC using the meta-analysis.Methods:Studies comparing elderly patients and nonelderly patients who underwent LG for GC were reviewed and collected from the PubMed, EBSCO, Cochrane Library, and EMBASE. Outcomes such as opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
0
22
0
4
Order By: Relevance
“…В связи с конституциональными особенностями популяции снижен порог ИМТ для ожирения (>25 кг/м 2 ). В некоторых публикациях азиатских авторов в группу старческого возраста включены пациенты старше 70 или даже 65 лет [63]. В большинстве РКИ в группы сравнения включены пациенты после неравнозначных по объему операций (ГЭ, ДРЖ, проксимальная резекция желудка, пилоруссохраняющая резекция желудка), что затрудняет интерпретацию результатов.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…В связи с конституциональными особенностями популяции снижен порог ИМТ для ожирения (>25 кг/м 2 ). В некоторых публикациях азиатских авторов в группу старческого возраста включены пациенты старше 70 или даже 65 лет [63]. В большинстве РКИ в группы сравнения включены пациенты после неравнозначных по объему операций (ГЭ, ДРЖ, проксимальная резекция желудка, пилоруссохраняющая резекция желудка), что затрудняет интерпретацию результатов.…”
Section: Discussionunclassified
“…Метаанализ Y. Pan et al 11 исследований, включивших 3275 пациентов из Кореи и Японии, показал, что у больных старческого возраста, по сравнению с более молодыми, вне ПУВ лапароскопический доступ сопровождался замедленным восстановлением перистальтики кишечника, более высоким риском общих послеоперационных, нехирургических и легочных осложнений, увеличением продолжительности госпитализации [63]. При этом в группе пациентов старческого возраста отмечены меньшая продолжительность операций (р = 0,002) и меньшее число удаленных лимфоузлов (р = 0,001).…”
Section: пув у пациентов пожилого и старческого возрастаunclassified
“…Another recent retrospective study of patients ≥ 80 years old who underwent transabdominal preperitoneal repair of groin hernia showed that the incidence of postoperative complication was influenced by poor performance status, lower hemoglobin level, and lower albumin level rather than old age [68]. Therefore, age alone should not preclude laparoscopic gastrectomy in elderly patients [69].…”
Section: Anesthesia In Elderly Patientsmentioning
confidence: 99%
“…Estos resultados han sido corroborados en metaanálisis que han resumido los resultados obtenidos en estos estudios randomizados [24][25][26][27] . La conclusión de ellos es que la cirugía laparoscópica en gastrectomía distal es estadísticamente similar a la cirugía abierta en cuanto a resultados a corto y largo plazo.…”
Section: Cirugía Mínimamente Invasiva En Cáncer Gástrico Incipienteunclassified